Ultrasound and X-ray-cholangiography diagnostic of Mirizzi syndrome - O. I. Okhotnikov; M. V. Yakovleva (Вестник рентгенологии и радиологии)
Objective: to improve the results of preoperative diagnosis of Mirizzi syndrome.Material and methods. Under our supervision for 2006–2015 we had 23 patients with the Mirizzi syndrome. Verification of cholecystolithiasis, condition of gallbladder’s wall and biliary tract dilatation degree was evaluated sonographically. Biliary decompression was realised by percutaneous transhepatic cholangiostomy that was implemented under the combined ultrasonic and X-ray control by the Seldinger technique for self-locking pigtail drainages 8 F. As a method for direct visualization of the bile ducts was used antegrade cholangiography. Results. Preoperative diagnosis was verified in 18 (78.3%) patients, based on the results of ultrasound and data of antegrade cholangiography. In I type of Mirizzi syndrome (prefistule form) was revealed a combination of non-standard ultrasonic symptoms: if there were signs of "high" extrahepatic block of bile ducts (area of liver gate and confluence of hepatic ducts) there was recorded actual intravesical bile hypertension. Lack of lymphadenopathy near the choledoch and focal lesions of liver parenchyma in the goal area confirmed the benign character of the "high" bile ducts block. II type of Mirizzi syndrome (fistula form) was characterized by the presence of megacholelitiasis combined with a lack of intravesical bile hypertension. Antegrade cholangiography in combination with intra-ductal diagnostic catheters and manipulation wires and in some cases with cholecystography allowed to differentiate types of Mirizzi syndrome. In 5 cases Mirizzi syndrome was an intraoperative finding. Antegrade minimal-invasive access to the biliary tree was used in patients with high risk of surgery for subsequent X-ray interventions (lithotripsy, balloon dilatation of major duodenal papilla, dislocation of stones to the duodenum).Conclusions. Effective preoperative diagnosis of Mirizzi syndrome can be successful more than in half cases of the combined use of ultrasonography of the biliary tract and the results of antegrade dynamic cholangiography. That was carried out through percutaneous transhepatic cholangiostomy in conjunction with additional diagnostic intraluminal manipulations (wires and catheter inspection and palpation).